Effects of temperature and relative humidity on growth of green leafhopper (Nephotettix virescens distant) - Tuan Yusof, Tuan Norizan (2018)
Green leafhopper (GLH), nephotettix virescens is one of the insects that attacks paddy plants in Malaysia. This species carries tungro virus that could damage the paddy plant. Early detection is important in order to manage and control the spreads of this virus. This study was conducted in order to find out the effect of weather parameters such as temperature and relative humidity (RH) to the population growth of green leafhoppers. A total of 27 samples of paddy plants at the age of 30 Days After Planting (DAP) were investigated. An instrument that consists of an embedded system was used to control temperature and RH. Fans and humidifiers were also installed to the embedded system to detect and control the level of temperatures and RH. Population number of GLH were counted and recorded on daily basis from nymph until adult stages. The sizes of GLH were also taken by using a digital camera (resolution of 750 pixels by 1334 pixels). The data was analyzed in MATLAB, whereas the sizes of GLH were monitored and discriminated based on controlled temperature and RH. The number of paddy leaves were also recorded to find out the relationship between the number of paddy leaves hosted by GLH with the temperature and RH. Statistical analysis was then performed to find out the significance differences between the treatments. Results indicated that there were differences between the treatments but not on the number of paddy leaves. Temperature and RH obtained from the instrumentation system indicated that higher GLH populations were found when the temperature was 30°C and RH was 80%. However, there were no relationship between the number of leaves attached by GLH with the weather parameters, and this indicated that at any values of temperatures and RH, GLH might be anywhere on the leaves. Based on the number of death of GLH, the mortality rate was counted. The survivability of GLH reduced when the temperature goes higher. There were higher mortality between day 19 to day 21 especially for the interactions of INT7 (temperature 40°C, RH 70%), INT8 (temperature 40°C, RH 80%), and INT9 (temperature 40°C, RH 90%). This study concluded that by knowing the meteorological data of temperature and RH, the GLH pest population can be forecasted in advance as an early warning mechanism to allow farmers to manage this pest in their farms. This preventive method of pest management can minimize the loss of yield in rice production due to pest and disease attack.